MEASURES FOR THE PREVENTION OF DOMESTIC VIOLENCE AND FOR THE PROTECTION OF VICTIMS IN SERBIA’S LEGAL SYSTEM WITH SPECIAL REFERENCE TO EMERGENCY MEASURES - Marković, Saša M. (NBP. Nauka, bezbednosti, policija, 2019)
Over the last two decades, combating domestic violence has been one of our country’s main goals. Serbia is one of the 12 countries that have ratified the Council of Europe Convention on Prevention and Combating Violence against Women and Domestic Violence (the Istanbul Convention) before its entry into force on August 1, 2014 as of June 1, 2017 the Law on the Prevention of Domestic Violence (LPDV) was used in Serbia, which was adopted with the aim of regulating in a general and uniform manner the organization and conduct of state authorities and institutions, thereby enabling the effective prevention of domestic violence and the prompt, timely and effective protection and support for victims of domestic violence. Prescribing emergency measures has radically changed the way victims of domestic violence are protected. In this paper, we will explore and try to answer several questions: what measures are available to state institutions to prevent violence and protect victims; whether the competent authorities and institutions apply these measures and to what extent; whether it was necessary to introduce urgent measures into our legal system and, finally, whether the activities to combat domestic violence so far produce results, that is, whether this negative social phenomenon is sufficiently suppressed. * Rad je rezultat istraživanja na projektu Ministarstva prosvete, nauke i tehnološkog razvoja Republike Srbije pod nazivom „Razvoj institucionalnih kapaciteta, standarda i procedura za suprostavlјanje organizovanom kriminalu i terorizmu u uslovima međunarodnih integracija“ br. 179045. * Docent, email: sasamarkovic975@gmail.com [1] Zakon o sprečavanju nasilјa u porodici, član 2.